A Study Of Effects Of Smoking On Lipid And Vitamin C Metabolism. A Pilot Study In Central Bihar. - KSHITISH KUMAR KSHITIZ; RAM BINAY SINHA; JAYASHREE BHATTACHARJEE (International Journal of Pharma and Bio Sciences, 2010)
Smoking is established cardiovascular disease risk factor. But the mechanism how it cause cardiovascular risk is still not properly understood. This study was aimed to evaluate lipid and vitamin C metabolism in chronic smokers from central Bihar, India for public enlightment. 60 male cigarette smokers and 20 male non-smokers were enrolled. It was found that mean serum Triglycerides (TG), Total cholesterol (TC), Low density lipoprotein cholesterol (LDL-C), Very low density lipoprotein cholesterol (VLDL-C) and urinary vitamin C were significantly higher in smokers as compared to non-smokers. Mean serum High density lipoprotein cholesterol (HDL-C) was significantly lower in smokers as compared to non-smokers. All these adverse effects may lead to serious metabolic diseases like atherosclerosis